The Impact of War on Handicraft Owners: A Case Study of Kassala State, Sudan - Fayga Hussein Ballal Awad; Yousif Jaffar Albashir Osman (International Journal of Social Science and Public Policy, 2026)
This study examines the economic and social effects of war on handicraft owners in Kassala State, Sudan. A total of 374 artisans participated in a structured questionnaire. Quantitative data were analyzed using SPSS (Version 26), employing descriptive statistics (frequencies, percentages, means, standard deviations) and Likert-scale analysis. Results indicate that 82.1% of participants reported reduced productivity due to the war, while 85.8% acknowledged increased production input costs. The proportion of respondents with a monthly income below 200 SDG rose sharply from 44.4% before the war to 83.7% during it. Additionally, 71.1% confirmed that handicrafts contributed to maintaining household economic and social stability during wartime. Regarding the displacement crisis, only 31.5% of artisans believed that displaced persons had positively impacted the craft sector, whereas 46.5% noted an increase in living costs and a decline in product quality. Availability of raw materials also dropped significantly from 85.6% pre-war to just 28.3% post-war. Furthermore, 80.2% of respondents relied solely on selling craft products for income. The study Recommends Enhancing access to raw materials through local sourcing policies, providing financial support and subsidies to artisans affected by conflict, integrating displaced persons into the craft sector through training and capacity-building, and supporting technical and vocational education for sustainable development. This study underscores the dual nature of handicrafts as both a resilience strategy and a vulnerable sector in conflict zones. Effective policy intervention is needed to support its continuity and social function.